2012
DOI: 10.1111/j.1365-2990.2011.01247.x
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus 71 encephalomyelitis and Japanese encephalitis can be distinguished by topographic distribution of inflammation and specific intraneuronal detection of viral antigen and RNA

Abstract: (2012) Neuropathology and Applied Neurobiology 38, 443-453 Enterovirus 71 encephalomyelitis and Japanese encephalitis can be distinguished by topographic distribution of inflammation and specific intraneuronal detection of viral antigen and RNA Aims: To investigate if two important epidemic viral encephalitis in children, Enterovirus 71 (EV71) encephalomyelitis and Japanese encephalitis (JE) whose clinical and pathological features may be nonspecific and overlapping, could be distinguished. Methods: Tissue s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 49 publications
3
21
0
Order By: Relevance
“…Macroscopically evident thalamic ‘degeneration’ similar to the necrolytic lesions in our case has been reported previously in chronic stages of MVE [8]. Although nonspecific, these necrolytic lesions may be more common or prominent in JE virus infection [9,10]. Brain MRI had also shown striking inflammation‐associated, thalamic hyperintensity in MVE, JE, TBE and WN encephalitis [11].…”
supporting
confidence: 86%
“…Macroscopically evident thalamic ‘degeneration’ similar to the necrolytic lesions in our case has been reported previously in chronic stages of MVE [8]. Although nonspecific, these necrolytic lesions may be more common or prominent in JE virus infection [9,10]. Brain MRI had also shown striking inflammation‐associated, thalamic hyperintensity in MVE, JE, TBE and WN encephalitis [11].…”
supporting
confidence: 86%
“…However, it is difficult to conduct these expensive examinations in a resource limiting setting in the rural areas of Asian countries. Neuropathological findings in fatal JEV cases showed that the virus caused broad inflammation in the central nervous system [33]. JEV infects neurons and causes direct damage [10,33] that consequently leads to many severe neurological symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathological findings in fatal JEV cases showed that the virus caused broad inflammation in the central nervous system [33]. JEV infects neurons and causes direct damage [10,33] that consequently leads to many severe neurological symptoms. Thus, in areas where E30 and JEV outbreaks are overlapping, severe neurological symptoms could provide strong evidence of JEV infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, in some infants and young children, after a few days of prodromal illness, HFMD caused predominantly by EV71 can be complicated by neurological manifestations, including ataxia, tremor, myoclonus, polio-like paralysis, encephalomyelitis, cardiopulmonary failure, and death (3,4). In humans with fatal EV71 encephalomyelitis, inflammation and viral antigens in neurons were observed mainly in the spinal cord, brainstem, hypothalamus, cerebellar dentate nucleus, and cerebrum (5,6). Since the 1970s, HFMD outbreaks with significant mortality have been reported throughout the world, including in Bulgaria in 1975 [44 deaths (7)], Hungary in 1978 [47 deaths (8) Appropriate animal models are needed to better understand EV71 neuropathogenesis and to facilitate the development of effective vaccines and drugs.…”
mentioning
confidence: 99%